Describing typeforms: a designer’s response - Dixon, Catherine (InfoDesign, 2008)
The paper sets out an overview of a pragmatic research investigation initiated within a doctoral enquiry, and which continues to inform design practice and pedagogy. Located within the fields of typography and information design, and very much concerned with design history, enquiry emphasized exploration of alternative design research methodologies in the production of a design outcome loaded with pedagogical ambition. The issue being addressed within the investigation was the limited scope of existing typeface classificatory systems to adequately describe the diversity of forms represented within current type design practice and thus, recent acquisitions to an established teaching collection in London. Addressing this issue unexpectedly came to utilize the researcher’s own design practice as a methodology for managing emergent enquiry, and for organizing and generating new knowledge through the employment of visual information management methods. A primary outcome of the enquiry was a new framework for the description of typeforms. This new framework will be described in terms of its operation, divergence from existing models and potential for application.